Von Willebrand Factor-cleaving Protease in Childhood Diarrhoea-associated Haemolytic Uraemic Syndrome - Hunt, Beverley J.; Lämmle, Bernhard; Nevard, Corinne H. F.; Haycock, George B.; Furlan, Miha (Thrombosis and Haemostasis, 2001)
A deficiency of von Willebrand factor (vWF)-cleaving protease, either due to a congenital deficiency or to the presence of a protease inhibitor of vWF-cleaving protease has been associated with thrombotic thrombocytopenic purpura (TTP). We have studied vWF-cleaving protease in diarrhoea-associated haemolytic uraemic syndrome (D+ HUS), which shares clinical features with TTP. 29 children with acute D+ HUS and 13 control children were studied.vWF-cleaving protease activity was normal (range 50-150%) in 39 of 42 plasma samples. Levels of protease activity between 25 and 50% were noted in plasma from two D+ HUS patients. One D+HUS patient, who had clinical features of TTP, had a vWF-cleaving protease inhibitor producing a severe deficiency of vWF-cleaving protease.Thus a deficiency of vWF-cleaving protease appears to be atypical in D+HUS. The detection of a vWF-cleaving protease inhibitor in one patient suggests it may be associated with infection such as E. coli 0157.
Keywords: Von Willebrand factor-cleaving protease; haemolytic uraemic syndrome